ENHANCING ENGLISH LANGUAGE PROFICIENCY IN GRADE 1 JUNIOR HIGH SCHOOL: THE IMPACT OF YOUTUBE VIDEOS AS A LEARNING TOOL - Muhammad Iqbal Tawaqal; Akbar Dwi Rizqyan (Mutiara Intelektual Indonesia Press, 2023)
The purpose of this large-scale study is to comprehensively investigate the effectiveness of adding YouTube videos as a pedagogical tool to improve the English language skills of first-year high school students. The purpose of the research is to provide a nuanced understanding of the benefits of using YouTube as a learning tool and to determine whether the videos that students watch significantly improve their English vocabulary comprehension, retention and cognitive processing. This study uses strong descriptive qualitative research and carefully focuses on first-year high school students. The primary method of data collection involves conducting in-depth interviews that provide a deep and comprehensible study of students experiences and insights into the transformative impact of YouTube videos on their journey to English language proficiency. The research findings undoubtedly emphasize the effective power of YouTube videos as an important educational tool. Students who regularly use YouTube to improve their English skills show not only remarkable but also transformational differences from those who occasionally watch such videos. Basically, students who actively participate in the consumption of YouTube videos show a significant expansion of their vocabulary, which proves the positive and tangible impact of this multimedia platform on language learning. The study carefully examines the benefits of seamlessly integrating YouTube into the language learning curriculum. Beyond the limitations of traditional pedagogical methods, YouTube and its inherently engaging audiovisual nature appeals to students and attention and at the same time different learning styles are taken into account, which promotes a dynamic and engaging language learning experience. Through carefully crafted open-ended questions, participants share their nuanced observations, preferences, and challenges they encounter using YouTube videos for language learning. Characterized by its richness and complexity, this qualitative data collection strategy provides a comprehensive understanding of the complex dynamics between students and engagement with YouTube. The research findings highlight the central role of YouTube in improving high school students' English language skills. Active integration of YouTube with students and study routines not only improve comprehension but also contribute to better retention of vocabulary. The sensory stimuli characteristic of YouTube videos stimulate cognitive processes, making it easier to enter and remember English words. In addition, the research findings emphasize the critical importance of developing a technologically enriched learning environment. Integrating YouTube into educational software not only acts as a catalyst for language acquisition, but also promotes digital literacy and adaptability, skills that are critical in today's educational environment. In conclusion, this comprehensive study provides invaluable insights into the effectiveness of YouTube videos as a catalyst for improving English language skills among first-year elementary school students. The findings highlight the paradigm-shifting impact of seamlessly integrating multimedia content into the language curriculum, prompting further research and providing important pedagogical considerations. As technology advances, harnessing the pedagogical potential of platforms like YouTube becomes a key strategy to create dynamic, engaging and highly effective language learning experiences for students.